2017
DOI: 10.1038/srep39888
|View full text |Cite|
|
Sign up to set email alerts
|

PHF14: an innate inhibitor against the progression of renal fibrosis following folic acid-induced kidney injury

Abstract: PHF14 is a newly identified regulator of mesenchyme growth in embryonic tissues. Previous studies have shown that phf14-null mutants die just after birth due to interstitial tissue hyperplasia in major organs, including the kidneys. The aim of this study was to investigate PHF14 function in renal fibrosis. By studying the chronic kidney injury mouse model, we found that PHF14 was upregulated in fibrotic kidneys after renal insults induced by folic acid administration. Compared with wild-type mice, PHF14-null m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In such a context, our present study identifies a PHF14/DNMT3B-mediated epigenetic mechanism via which SMAD7 transcription is suppressed in LAD. Consistently, previous studies have found that the expression of DNMT3B and PHF14 can be elevated following TGF-β stimulation 45 , 46 . Moreover, our data unveil that the transcriptional status of SMAD7 in LAD is jointly regulated by TGF-β signaling-mediated transcriptional activation and PHF14/DNMT3B-mediated transcriptional suppression.…”
Section: Discussionsupporting
confidence: 90%
“…In such a context, our present study identifies a PHF14/DNMT3B-mediated epigenetic mechanism via which SMAD7 transcription is suppressed in LAD. Consistently, previous studies have found that the expression of DNMT3B and PHF14 can be elevated following TGF-β stimulation 45 , 46 . Moreover, our data unveil that the transcriptional status of SMAD7 in LAD is jointly regulated by TGF-β signaling-mediated transcriptional activation and PHF14/DNMT3B-mediated transcriptional suppression.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we report an additional interactor of HMG20A, the histone reader PHF14, which has also been associated with mesenchymal growth ( 16–18 ). Knockout of PHF14 in mice results in neonatal lethality due to defects in several organs including fibrosis in kidney and lung ( 16 , 19 ). We have now characterized the HMG20A-PHF14 complex molecularly and in silico and show that HMG20A and PHF14 share common functions in controlling the transcriptome, cell migration and invasion and cell-cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of PHF14 accelerates growth of BTC cells [23]. PHF14 inhibits renal fibrosis after kidney injury induced by folic acid [24]. Depletion of PHF14 inhibits cancer cell proliferation and tumorigenesis in lung cancer [25].…”
Section: Introductionmentioning
confidence: 99%